Evolution of nucleophilic high molecular-weight organic compounds in ambient aerosols: a case study - C. He; H. Che; Z. Bao; Y. Liu; Q. Li; M. Hu; J. Zhou; S. Zhang; X. Yao; Q. Shi; C. Chen; Y. Han; et al. (Atmospheric Chemistry and Physics, 2024)
Nucleophilic high molecular-weight organic compounds (HMWOCs) are sensitive to protons (H+) in Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) analysis. A comprehensive evaluation of the diurnal evolution of nucleophilic HMWOCs was performed. HMWOCs aged significantly in daily cycles, accompanied by functionality shifts, particularly oxygenated and reduced nitrogen (CHON and CHN) as well as oxygenated organics. The intensities of high molecular-weight (HMW) oxygenated compounds increased during both daytime and nighttime. The daytime evolution produced more nitrogen-containing compounds with carboxylic group (–COOH) homologues with molecular weights greater than 300, while the nighttime evolution produced mostly small CHON compounds (molecular weights < 300). During evolution, nighttime CHON removals were observed; meanwhile, carboxylation was also identified in CHON groups. The daytime evolution produced significantly more reduced-nitrogen-containing compounds; a day- and nighttime increase in CHN compounds with five members was also observed. This study can provide insights into the aging of less polar organic aerosols.